Inflammatory Fibroid Polyp of the Stomach Mimics Malignancy on 18F FDG PET/CT Imaging. (September 2016) - Bilgin, Sabriye Sennur; Bilgin, Mehmet; Savas, Recep; Erdogan, Ezgi Basak
Abstract : Abstract: Inflammatory fibroid polyps (IFPs) are rare non-neoplastic and proliferating submucosal lesions of the gastrointestinal tract. The classic IFP, which was first described by Vanek, consists of prominent blood vessels and is characterized by a heavy inflammatory infiltrate, which is rich in eosinophilic granulocytes. The clinical presentation depends on the size and location. Inflammatory fibroid polyps cannot be differentiated from malignancy without histological examination. We report a case of IFP in the stomach that mimicked a primary gastric malignancy showing an increased 18 F-FDG uptake.